Artificial stone efflorescence-resistant material as well as preparation method and application thereof

By using zinc-tungsten composite smelting slag and other components in artificial stone, the problem of alkali-panning caused by cement-based cementitious materials is solved, and a longer-term effect of inhibiting alkali-panning and higher strength and wear resistance are achieved.

CN119822778APending Publication Date: 2025-04-15CHINA RESOURCES CEMENT TECH RES DEV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510125248.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Due to the use of cement-based cementitious materials, existing inorganic artificial stones have pores and alkaline hydration products that appear as the moisture evaporates, forming alkaline, affecting the aesthetic effect of the surface.

Method used

Using an artificial stone anti-alkali material, its raw material components include cement, slag powder, gypsum, zinc-tungsten composite smelting slag and premature strength agent. By preparing zinc-tungsten composite smelting slag, CaO and triethanolamine are added and ground to form a hydrated calcium silicate phase and hydrotalcite phase with a low Ca/Si ratio to reduce the formation of alkaline hydration products.

Benefits of technology

Effectively inhibit the alkaline phenomenon of artificial stone, reduce raw material costs, extend the service life of artificial stone, and improve its strength and wear resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005259882170000131
    Figure BDA0005259882170000131
  • Figure BDA0005259882170000141
    Figure BDA0005259882170000141
  • Figure BDA0005259882170000142
    Figure BDA0005259882170000142
Patent Text Reader

Abstract

The invention provides an artificial stone efflorescence-resistant material and a preparation method and application thereof, and relates to the technical field of solid waste resource utilization, the artificial stone efflorescence-resistant material comprises the following raw material components: cement, slag powder, gypsum, zinc-tungsten composite smelting slag and an early strength agent, the zinc-tungsten composite smelting slag is prepared by adding CaO and triethanolamine into mixed powder of zinc smelting slag and tungsten smelting slag and mixing. The artificial stone efflorescence-resistant material is mainly prepared from industrial waste residues through a special process and can directly replace an artificial stone cementing material, generation of alkaline hydration products in the artificial stone is greatly reduced from the source, meanwhile, due to the excellent grading and water retention performance of the efflorescence-resistant material, after the artificial stone is installed, water in the artificial stone is little evaporated, and the service life of the artificial stone is prolonged. According to the present invention, the problem of the recycling of the zinc smelting slag and tungsten smelting slag industrial solid waste can be solved, and the low-cost reliable alkali efflorescence resistance material can be provided for the artificial stone industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid waste resource utilization, and in particular to an artificial stone anti-efflorescence material and a preparation method and application thereof. Background Art

[0002] Artificial stone is a kind of artificially synthesized decorative material. According to the different adhesives used, it is divided into two categories: inorganic artificial stone and organic artificial stone. Among them, inorganic artificial stone is a material that is made by a special manufacturing process with inorganic powder, filler, pigment and special additives as the main raw materials. It is used more and more widely because of its high durability and excellent plasticity, denser internal structure, similar appearance and texture to natural stone, better hardness, wear resistance, corrosion resistance and other properties. However, the existing inorganic artificial stone uses cement as a cementitious material. In order to obtain higher strength, more water is needed to mix. After hardening, more pores are generated inside the stone. The alkaline hydration products generated by hardening gradually overflow from the pores to the surface of the stone as the water inside the artificial stone evaporates, reacting with acidic substances in the air to generate salts, condensing on the decorative surface layer, forming crystalline substances, thereby causing efflorescence, which seriously affects the aesthetic effect of the surface of the artificial stone.

[0003] At present, in order to prevent artificial stone from efflorescence, stone protective agent is mainly applied on the six surfaces of artificial stone in advance. The organic silicon and organic fluorine components in the stone protective agent enter the interior of the stone through the solvent. After the solvent evaporates, it combines with the stone's own substances through chemical bonds to form a mesh protective layer and firmly bond with the stone, thereby preventing the entry of external moisture and acidic substances, preventing the seepage of alkaline substances in the cement mortar on the bonding surface, and preventing the alkaline substances inside the stone from migrating to the surface with the evaporation of water, thereby achieving the effect of inhibiting efflorescence.

[0004] The use of stone protective agents to inhibit efflorescence of artificial stones has the following main disadvantages: 1. The protective agent has a short service life, and the effect of inhibiting efflorescence is limited, and it needs to be re-applied frequently. This is mainly because the strong alkaline substances on the surface and inside of inorganic artificial stones will cause the alkali-intolerant organic matter in the protective agent to degrade and fail, and the capillary pores of artificial stones are small. Most of the protective agents applied with protective agents form a film on the surface of the stone. After being washed by rain and invaded by the external humid environment, the film-forming substances will peel off, and the protection will gradually fail; 2. The construction process of using protective agents is complicated and inefficient. When using stone protective agents, it is necessary to apply them on the six surfaces of the stone before installing the stone. The operation process is complicated, the degree of automation is low, the brushing effect is not ideal, and it consumes a lot of manpower. 3. Stone protective agents are expensive. At present, the commonly used stone protective agents on the market are mainly three categories: organic siloxane, organic fluorosilicone polymer and resin. The above three types of raw materials are expensive and need to be prepared by complex organic synthesis processes, resulting in high cost of protective agents.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One of the purposes of the present invention is to provide an artificial stone anti-efflorescence material to at least solve one of the technical problems existing in the prior art. The artificial stone anti-efflorescence material provided by the present invention can replace cement-based cementitious materials in inorganic artificial stone, reduce the generation of efflorescence substances such as calcium hydroxide, and inhibit the efflorescence of artificial stone while ensuring the excellent performance of artificial stone.

[0007] The second object of the present invention is to provide a method for preparing an artificial stone anti-efflorescence material. The preparation method provided by the present invention prepares a non-cement-based cementitious material that can inhibit artificial stone efflorescence.

[0008] The third object of the present invention is to provide an artificial stone anti-efflorescence material for use in the preparation of artificial stone.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] In a first aspect, the present invention provides an artificial stone anti-efflorescence material, wherein the raw material components thereof include, by weight: 17.0-27.5 parts by weight of cement, 19-39.5 parts by weight of slag powder, 2.5-12.5 parts by weight of gypsum, 30-50 parts by weight of zinc-tungsten composite smelting slag and 0.5-1.5 parts by weight of an early strength agent;

[0011] The zinc-tungsten composite smelting slag is prepared by adding CaO and triethanolamine to a mixed powder of zinc smelting slag and tungsten smelting slag.

[0012] Furthermore, the components of the zinc-tungsten composite smelting slag include zinc smelting slag and tungsten smelting slag;

[0013] Preferably, the components of the zinc-tungsten composite smelting slag include, by mass, 65-75 parts by mass of zinc smelting slag and 25-35 parts by mass of tungsten smelting slag;

[0014] Preferably, the specific surface area of ​​the zinc-tungsten composite smelting slag is 500±10㎡ / kg;

[0015] Furthermore, the amount of CaO added is 0.5%-1.5% of the total weight of the mixed powder;

[0016] Preferably, the added amount of triethanolamine is 0.5%-1.5% of the total weight of the mixed powder.

[0017] Furthermore, the cement includes silicate cement.

[0018] Furthermore, the specific surface area of ​​the slag powder is 650±10㎡ / kg;

[0019] Preferably, the slag powder is obtained by grinding granulated blast furnace slag in a ball mill;

[0020] Preferably, the particle size of the granulated blast furnace slag is 2 μm-105 μm.

[0021] Further, the gypsum includes at least one of dihydrate gypsum, desulfurized gypsum and phosphogypsum;

[0022] Preferably, the specific surface area of ​​the gypsum is 450±10 m2 / kg.

[0023] Furthermore, the early strength agent includes at least one of sodium sulfate, sodium hydroxide and calcium chloride.

[0024] In a second aspect, the present invention provides a method for preparing an artificial stone anti-efflorescence material, comprising the following steps:

[0025] The artificial stone anti-efflorescence material is obtained by mixing the formulated amounts of cement, slag powder, gypsum, zinc-tungsten composite smelting slag and early strength agent.

[0026] Furthermore, the zinc-tungsten composite smelting slag is prepared by the following steps:

[0027] Adding CaO and triethanolamine to a mixed powder of zinc smelting slag and tungsten smelting slag, and grinding the mixture to obtain the zinc-tungsten composite smelting slag;

[0028] Preferably, before the zinc smelting slag and the tungsten smelting slag are mixed, the zinc smelting slag and the tungsten smelting slag are dried to a moisture content of ≤0.5% respectively;

[0029] Preferably, during the preparation of the artificial stone anti-efflorescence material, the mixing time is ≥ 20 min.

[0030] In a third aspect, the present invention provides an application of an artificial stone anti-efflorescence material in the preparation of artificial stone.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] The artificial stone anti-efflorescence material provided by the present invention has a low raw material cost and can be directly used to replace the artificial stone cementitious material, greatly reducing the generation of alkaline hydration products in the artificial stone from the source. The zinc-tungsten composite smelting slag in its components uses zinc smelting slag and tungsten smelting slag as raw materials, and CaO and triethanolamine are added. After a special grinding process, the activity of the zinc smelting slag and the tungsten smelting slag can be stimulated. After being mixed with slag powder, gypsum and a small amount of cement and adding water, a hydrated calcium silicate phase and a hydrotalcite phase with a low Ca / Si ratio are formed, which reduces the generation of alkaline hydration products such as Ca(OH)2 from the source, greatly reduces the calcium hydroxide that migrates to the surface with water evaporation, and effectively inhibits efflorescence. At the same time, due to the excellent grading and water retention performance of the anti-efflorescence material, the water demand in the preparation process of artificial stone is reduced, the internal structure of the artificial stone is more compact, the capillary pores are reduced, and after the artificial stone is installed, the internal water evaporates less, the alkaline hydration products that migrate out are less, and there is basically no efflorescence phenomenon. DETAILED DESCRIPTION

[0033] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The first aspect of the present invention provides an artificial stone anti-efflorescence material, the raw material components of which include: cement, slag powder, gypsum, zinc-tungsten composite smelting slag and early strength agent;

[0036] The zinc-tungsten composite smelting slag is prepared by adding CaO and triethanolamine to a mixed powder of zinc smelting slag and tungsten smelting slag.

[0037] The artificial stone anti-efflorescence material provided by the present invention has a low raw material cost and can be directly used to replace the artificial stone cementitious material, thereby greatly reducing the generation of alkaline hydration products in the artificial stone from the source. At the same time, due to the excellent grading and water retention performance of the anti-efflorescence material, the water demand in the preparation process of the artificial stone is reduced, the internal structure of the artificial stone is more compact, the capillary pores are reduced, and after the artificial stone is installed, the internal water evaporates less, the alkaline hydration products that migrate out are less, and there is basically no efflorescence phenomenon.

[0038] The artificial stone anti-efflorescence material provided by the present invention is prepared from industrial solid waste, and the product cost is low. Compared with the traditional stone protective agent, the anti-efflorescence cost is significantly reduced. The anti-efflorescence material provided by the present invention is mainly composed of industrial solid wastes such as zinc-tungsten composite smelting slag, slag powder, gypsum, etc., which can significantly reduce the raw material cost of the product. At the same time, when used in artificial stone, it can 100% replace cement to prepare artificial stone, and can also reduce the manufacturing cost of artificial stone, generating greater economic benefits.

[0039] The raw material components of the artificial stone anti-efflorescence material provided by the present invention include, by weight:

[0040] 17.0-27.5 parts by weight of cement, 19-39.5 parts by weight of slag powder, 2.5-12.5 parts by weight of gypsum, 30-50 parts by weight of zinc-tungsten composite smelting slag and 0.5-1.5 parts by weight of early strength agent, the total amount of the above raw materials is 100 parts by weight.

[0041] Based on 100 parts by weight of the total artificial stone anti-efflorescence material, the added amount of the cement is 17.0-27.5 parts by weight, for example, 17 parts by weight, 18 parts by weight, 19 parts by weight, 20 parts by weight, 21 parts by weight, 22 parts by weight, 23 parts by weight, 24 parts by weight, 25 parts by weight, 26 parts by weight, 27 parts by weight, 27.5 parts by weight, etc.;

[0042] Based on 100 parts by weight of the total artificial stone anti-efflorescence material, the added amount of the slag powder is 19-39.5 parts by weight, for example, 19 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 39.5 parts by weight, etc.;

[0043] Based on 100 parts by weight of the total weight of the artificial stone anti-efflorescence material, the added amount of the gypsum is 2.5-12.5 parts by weight, for example, it can be 2.5 parts by weight, 3 parts by weight, 3.5 parts by weight, 4 parts by weight, 4.5 parts by weight, 5 parts by weight, 5.5 parts by weight, 6 parts by weight, 6.5 parts by weight, 7 parts by weight, 7.5 parts by weight, 8 parts by weight, 8.5 parts by weight, 9 parts by weight, 9.5 parts by weight, 10 parts by weight, 10.5 parts by weight, 11 parts by weight, 11.5 parts by weight, 12 parts by weight, 12.5 parts by weight, etc.;

[0044] Based on 100 parts by weight of the total artificial stone anti-efflorescence material, the addition amount of the zinc-tungsten composite smelting slag is 30-50 parts by weight, for example, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight, 50 parts by weight, etc.;

[0045] Based on 100 parts by weight of the total artificial stone anti-efflorescence material, the addition amount of the early strength agent is 0.5-1.5 parts by weight, for example, it can be 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight, 1 part by weight, 1.1 parts by weight, 1.2 parts by weight, 1.3 parts by weight, 1.4 parts by weight, 1.5 parts by weight, etc.

[0046] In some preferred embodiments, the components of the zinc-tungsten composite smelting slag include zinc smelting slag and tungsten smelting slag;

[0047] In the present invention, zinc smelting slag and tungsten smelting slag are compounded to prepare a non-cement-based gelling material, which can be applied to the field of comprehensive recycling of solid waste to prepare high-end building materials.

[0048] Preferably, the components of the zinc-tungsten composite smelting slag include, by mass, 65-75 parts by mass of zinc smelting slag and 25-35 parts by mass of tungsten smelting slag;

[0049] Based on 100 parts by weight of the total zinc-tungsten composite smelting slag, the addition amount of the zinc smelting slag is 65-75 parts by weight, for example, 65 parts by weight, 66 parts by weight, 67 parts by weight, 68 parts by weight, 69 parts by weight, 70 parts by weight, 71 parts by weight, 72 parts by weight, 73 parts by weight, 74 parts by weight, 75 parts by weight, etc.;

[0050] Based on 100 parts by mass of the total zinc-tungsten composite smelting slag, the added amount of the tungsten smelting slag is 25-35 parts by mass, for example, it can be 25 parts by mass, 26 parts by mass, 27 parts by mass, 28 parts by mass, 29 parts by mass, 30 parts by mass, 31 parts by mass, 32 parts by mass, 33 parts by mass, 34 parts by mass, 35 parts by mass, etc.

[0051] Preferably, the specific surface area of ​​the zinc-tungsten composite smelting slag is 500±10㎡ / kg, for example, it can be 490㎡ / kg, 500㎡ / kg, 510㎡ / kg, etc.;

[0052] The zinc-tungsten composite smelting slag is prepared by adding CaO and triethanolamine to a mixed powder of zinc smelting slag and tungsten smelting slag;

[0053] In the present invention, when preparing the zinc-tungsten composite smelting slag, CaO provides an alkaline environment. When it meets water, the silicon-oxygen bonds and aluminum-oxygen bonds in the aluminosilicate minerals in the zinc-tungsten composite smelting slag are easily broken, and silicon and aluminum ions are released from the mineral structure. A polymerization reaction occurs in the alkaline environment to form negatively charged silicate ions ([SiO4] 4- ) and aluminate ions ([AlO4] 5-), these ions further polymerize by sharing oxygen atoms to form a three-dimensional network of aluminosilicate gel structure, thus forming certain gelling properties; triethanolamine can play a role in grinding and optimize the grading of smelting slag, and at the same time it can complex the Fe and Al phases in the smelting slag. In the alkaline environment provided by CaO, the surface of the smelting slag is easy to depolymerize, and it is gradually destroyed from the surface to the inside, releasing active Al2O3 and active SiO2, and reacting with CaO. 2+ The reaction forms more hydration products, which increases the strength of the material.

[0054] Preferably, the addition amount of CaO is 0.5%-1.5% of the total weight of the mixed powder, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.;

[0055] Preferably, the added amount of triethanolamine is 0.5%-1.5% of the total weight of the mixed powder, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.

[0056] In some preferred embodiments, the cement comprises Portland cement.

[0057] In the present invention, cement is commercially available general-purpose Portland cement of grade PII52.5.

[0058] In some preferred embodiments, the specific surface area of ​​the slag powder is 650±10㎡ / kg, for example, 640㎡ / kg, 650㎡ / kg, 660㎡ / kg, etc.;

[0059] Preferably, the slag powder is obtained by grinding granulated blast furnace slag in a ball mill;

[0060] In the present invention, the slag powder is obtained by grinding granulated blast furnace slag in a ball mill to a powder having a specific surface area of ​​650±10㎡ / kg.

[0061] The artificial stone anti-efflorescence material provided by the present invention has a longer-lasting anti-efflorescence effect. The artificial stone is prepared by directly using an artificial stone anti-efflorescence material prepared from a zinc-tungsten composite smelting slag as a raw material. Due to its fineness and high specific surface area, the artificial stone is filled more densely. At the same time, due to the reduced water demand and low initial heat release during the hydration process, the formed calcium silicate hydrate phase and hydrotalcite phase with a low Ca / Si ratio have a high degree of crystallization, making the internal structure of the artificial stone denser, the strength higher, the water evaporation less, the internal and external acidic and alkaline substances are difficult to erode, and the surface structure is not easy to break, thereby extending the service life of the artificial stone and achieving a longer-lasting anti-efflorescence effect.

[0062] Preferably, the particle size of the granulated blast furnace slag is 2 μm-105 μm, for example, it can be 2 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 105 μm, etc.

[0063] In some preferred embodiments, the gypsum includes at least one of industrial dihydrate gypsum, process byproduct desulfurization gypsum and phosphogypsum;

[0064] Preferably, the specific surface area of ​​the gypsum is 450±10 m2 / kg, for example, 440 m2 / kg, 450 m2 / kg, 460 m2 / kg, etc.

[0065] In some preferred embodiments, the early strength agent includes at least one of sodium sulfate, sodium hydroxide and calcium chloride.

[0066] In a second aspect, the present invention provides a method for preparing the artificial stone anti-efflorescence material, comprising the following steps:

[0067] The artificial stone anti-efflorescence material is obtained by mixing the formulated amounts of cement, slag powder, gypsum, zinc-tungsten composite smelting slag and early strength agent.

[0068] In the present invention, the artificial stone anti-efflorescence material is mainly prepared by a special process using industrial waste slag. The artificial stone anti-efflorescence material provided by the present invention can not only solve the problem of recycling industrial solid waste of zinc smelting slag and tungsten smelting slag, but also provide a low-cost and reliable anti-efflorescence material for the artificial stone industry.

[0069] Preferably, during the preparation of the artificial stone anti-efflorescence material, the mixing time is ≥ 20 min.

[0070] In some preferred embodiments, the zinc-tungsten composite smelting slag is prepared by the following steps:

[0071] Adding CaO and triethanolamine to a mixed powder of zinc smelting slag and tungsten smelting slag, and grinding the mixture to obtain the zinc-tungsten composite smelting slag;

[0072] Preferably, before the zinc smelting slag and the tungsten smelting slag are mixed, the zinc smelting slag and the tungsten smelting slag are dried to a moisture content of ≤0.5% respectively;

[0073] In the present invention, the preparation process of zinc-tungsten composite smelting slag specifically includes: adding zinc-tungsten smelting slag into a ball mill according to a certain ratio, grinding for 5 minutes, and then adding 0.5-1.5% CaO and 0.5-1.5% triethanolamine according to the total weight of the powder, and continuing to grind until the powder specific area reaches 500±10㎡ / kg, so as to obtain zinc-tungsten composite smelting slag. The present invention reduces the generation of alkaline hydration products from the source, greatly reduces the calcium hydroxide that migrates to the surface with the evaporation of water, and effectively inhibits alkali efflux. After adding CaO and triethanolamine to zinc smelting slag and tungsten smelting slag and undergoing a special grinding process, the activity of zinc smelting slag and tungsten smelting slag can be stimulated. After being mixed with slag powder, gypsum and a small amount of cement and adding water, the alkali metal oxides in the powder are dissolved into ionic state, so that the pH value of the system is continuously increased, and the covalent bonds of Si-O-Si and Al-O-Si in the original ore are broken, and they are re-bonded with CaO and triethanolamine. 2+ 、Na + The new phase gradually develops a dense structure, and the strong alkaline hydration products such as Ca(OH)2 in the hydration products are greatly reduced and will not migrate to the surface of the artificial stone for crystallization.

[0074] In a third aspect, the present invention provides a use of the artificial stone anti-efflorescence material in the preparation of artificial stone.

[0075] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.

[0076] In the following examples and comparative examples, the cement used is commercially available general-purpose Portland cement of grade PII52.5.

[0077] Example 1

[0078] This embodiment provides an artificial stone anti-efflorescence material, and its raw material components include, by weight:

[0079] 27.5 parts by weight of PII cement, 39.5 parts by weight of slag powder, 2.5 parts by weight of gypsum, 30 parts by weight of zinc-tungsten composite smelting slag and 0.5 parts by weight of early strength agent.

[0080] Example 2

[0081] This embodiment provides an artificial stone anti-efflorescence material, and its raw material components include, by weight:

[0082] 26 parts by weight of PII cement, 32.5 parts by weight of slag powder, 4.2 parts by weight of gypsum, 36.5 parts by weight of zinc-tungsten composite smelting slag and 0.8 parts by weight of early strength agent.

[0083] Example 3

[0084] This embodiment provides an artificial stone anti-efflorescence material, and its raw material components include, by weight:

[0085] 25.2 parts by weight of PII cement, 30.8 parts by weight of slag powder, 6.5 parts by weight of gypsum, 36.5 parts by weight of zinc-tungsten composite smelting slag and 1.0 part by weight of early strength agent.

[0086] Example 4

[0087] This embodiment provides an artificial stone anti-efflorescence material, and its raw material components include, by weight:

[0088] 23.5 parts by weight of PII cement, 28.5 parts by weight of slag powder, 8.8 parts by weight of gypsum, 38 parts by weight of zinc-tungsten composite smelting slag and 1.2 parts by weight of early strength agent.

[0089] Example 5

[0090] This embodiment provides an artificial stone anti-efflorescence material, and its raw material components include, by weight:

[0091] 21 parts by weight of PII cement, 27.2 parts by weight of slag powder, 10.0 parts by weight of gypsum, 40.5 parts by weight of zinc-tungsten composite smelting slag and 1.3 parts by weight of early strength agent.

[0092] Example 6

[0093] This embodiment provides an artificial stone anti-efflorescence material, and its raw material components include, by weight:

[0094] 18.5 parts by weight of PII cement, 24 parts by weight of slag powder, 11.0 parts by weight of gypsum, 45.0 parts by weight of zinc-tungsten composite smelting slag and 1.5 parts by weight of early strength agent.

[0095] Example 7

[0096] This embodiment provides an artificial stone anti-efflorescence material, and its raw material components include, by weight:

[0097] 17 parts by weight of PII cement, 19 parts by weight of slag powder, 12.5 parts by weight of gypsum, 50 parts by weight of zinc-tungsten composite smelting slag and 1.5 parts by weight of early strength agent.

[0098] It should be noted that in the above embodiments 1-7:

[0099] The slag powder is obtained by grinding granulated blast furnace slag with a particle size of 2μm-105μm in a ball mill to a specific surface area of ​​650㎡ / kg. The gypsum is obtained by grinding industrial dihydrate gypsum to a specific surface area of ​​450㎡ / kg.

[0100] The specific surface area of ​​the zinc-tungsten composite smelting slag is 500 m2 / kg. The zinc-tungsten composite smelting slag includes 70 parts by mass of zinc smelting slag and 30 parts by mass of tungsten smelting slag. The zinc smelting slag and the tungsten smelting slag are ground to obtain a mixed powder. The amount of CaO added is 1% of the total weight of the powder, and the amount of triethanolamine added is 1% of the total weight of the powder.

[0101] The early strength agent is sodium sulfate.

[0102] Example 8

[0103] This embodiment provides an artificial stone anti-efflorescence material, which is different from Embodiment 7 in that:

[0104] The specific surface area of ​​slag powder is 640㎡ / kg, and the gypsum adopts desulfurized gypsum which is a by-product of the process, and the specific surface area of ​​gypsum is 440㎡ / kg;

[0105] The specific surface area of ​​the zinc-tungsten composite smelting slag is 490 m2 / kg. The zinc-tungsten composite smelting slag includes 65 parts by mass of zinc smelting slag and 35 parts by mass of tungsten smelting slag. The amount of CaO added is 0.5% of the total weight of the powder, and the amount of triethanolamine added is 1.5% of the total weight of the powder.

[0106] The early strength agent is sodium hydroxide;

[0107] The rest is consistent with Example 7.

[0108] Example 9

[0109] This embodiment provides an artificial stone anti-efflorescence material, which is different from Embodiment 7 in that:

[0110] The slag powder has a specific surface area of ​​660㎡ / kg, and the gypsum uses phosphogypsum, and the specific surface area of ​​gypsum is 460㎡ / kg;

[0111] The specific surface area of ​​the zinc-tungsten composite smelting slag is 510 m2 / kg. The zinc-tungsten composite smelting slag includes 75 parts by mass of zinc smelting slag and 25 parts by mass of tungsten smelting slag. The amount of CaO added is 1.5% of the total weight of the powder, and the amount of triethanolamine added is 0.5% of the total weight of the powder.

[0112] The early strength agent is calcium chloride.

[0113] Examples 10-18

[0114] Embodiments 10-18 provide a method for preparing an artificial stone anti-efflorescence material, which is prepared using the component formulas in Embodiments 1-9, respectively, and comprises the following steps:

[0115] (1) Preparation of zinc-tungsten composite smelting slag: The zinc smelting slag and tungsten slag of the formulated amount are dried to a moisture content of ≤0.5%, added into a ball mill, and ground for 5 minutes, and then CaO and triethanolamine are added according to the total weight of the powder, and the grinding is continued until the powder reaches a predetermined specific area, thereby obtaining zinc-tungsten composite smelting slag;

[0116] (2) Grinding slag powder and gypsum separately: Grinding purchased granulated blast furnace slag with a particle size of 2 μm-105 μm in a ball mill to a powder with a predetermined specific surface area, and grinding gypsum to a predetermined specific surface area;

[0117] (3) Place the formulated amount of cement, slag powder, gypsum, zinc-tungsten composite smelting slag and early strength agent into a horizontal mixer and stir for more than 20 minutes until the powder is uniform and stable, which is the artificial stone anti-efflorescence material.

[0118] Application Examples 1-9

[0119] Application Examples 1-9 provide an application of an artificial stone anti-efflorescence material in the preparation of artificial stone. Application Examples 1-9 respectively use the artificial stone anti-efflorescence material prepared in Examples 10-18 to 100% replace the cementitious material in the inorganic artificial quartz stone to prepare the inorganic artificial stone. The preparation method of the inorganic artificial stone is: according to the artificial stone formula requirements, various raw materials including the artificial stone anti-efflorescence material are prepared, stirred and mixed, and then water is added to a plastic state, and then the material is spread, pressed into shape, and then cured. After curing to a certain age, it is polished and cut to obtain the finished artificial stone.

[0120] Comparative Example 1

[0121] This comparative example provides an artificial stone anti-efflorescence material, which is different from Example 7 in that:

[0122] 28 parts by weight of PII cement, 40 parts by weight of slag powder, 2 parts by weight of gypsum, 28 parts by weight of zinc-tungsten composite smelting slag and 2 parts by weight of early strength agent.

[0123] Comparative Example 2

[0124] This comparative example provides an artificial stone anti-efflorescence material, which is different from Example 7 in that:

[0125] 16.6 parts by weight of PII cement, 18 parts by weight of slag powder, 14 parts by weight of gypsum, 51 parts by weight of zinc-tungsten composite smelting slag and 0.4 parts by weight of early strength agent.

[0126] Comparative Example 3

[0127] This comparative example provides an artificial stone anti-efflorescence material, which is different from Example 7 in that:

[0128] In the process of preparing zinc-tungsten composite smelting slag, no CaO is added, and the amount of triethanolamine added is 2% of the total weight of the powder. The rest is consistent with Example 7.

[0129] Comparative Example 4

[0130] This comparative example provides an artificial stone anti-efflorescence material, which is different from Example 7 in that:

[0131] In the process of preparing zinc-tungsten composite smelting slag, triethanolamine is not added, the amount of CaO added is 2% of the total weight of the powder, and the rest is consistent with Example 7.

[0132] Comparative Examples 5-8

[0133] Comparative Examples 5-8 provide a preparation method for an artificial stone anti-efflorescence material, which is prepared using the component formulas in Comparative Examples 1-4 respectively, and the preparation method is consistent with the preparation method of Example 16.

[0134] Comparative Application Examples 1-4

[0135] Comparative Application Examples 1-4 provide an application of an artificial stone anti-efflorescence material in the preparation of artificial stone. The artificial stone anti-efflorescence material prepared in Comparative Examples 5-8 is used to 100% replace the cementitious material in the inorganic artificial quartz stone to prepare the inorganic artificial stone. The preparation method of the inorganic artificial stone is consistent with that of Application Example 7.

[0136] Comparative Application Example 5

[0137] In comparative application example 5, inorganic artificial quartz stone is prepared by using a conventional material formula using cement as a gelling material, and a commercially available anti-efflorescence protective agent is applied on the outside of the inorganic artificial quartz stone.

[0138] Table 1 shows the composition ratios of the artificial stone anti-efflorescence materials in the examples of the present invention and the comparative examples.

[0139] Table 1

[0140]

[0141]

[0142] Test Case

[0143] Test samples: The inorganic artificial stone prepared in Application Examples 1-9 and the artificial stone prepared in Comparative Application Examples 1-5 were used as test samples.

[0144] Test method: The performance test was carried out according to Q-HQJD 001-2020 "Inorganic artificial stone slabs". The test results are shown in Table 2.

[0145] Table 2

[0146]

[0147] As can be seen from the data in Table 2, in Comparative Application Example 5, the traditional stone protective agent was used to brush the artificial stone to inhibit efflorescence. It was found that the efflorescence area of ​​the artificial stone was about 30%, and the efflorescence was still serious and could not meet the standard requirements. The wear resistance of the surface of the artificial stone was also poor and it was easy to wear. Some of the raw material components in Comparative Application Examples 1-4 are not within the scope of the present invention, and the products thereof will have poor efflorescence resistance, high water absorption, low bending strength and other problems, and it cannot be guaranteed that all properties meet the standard value requirements. The materials in Application Examples 1-9 are used in the preparation of inorganic artificial stone, which makes the artificial The water absorption rate of the stone is significantly reduced, the bending strength is increased, and the linear expansion coefficient is reduced, indicating that the artificial stone structure prepared by the method is denser and has fewer pores, and the efflorescence area of ​​the artificial stone is also significantly reduced, proving that the anti-efflorescence material prepared by the present invention can greatly reduce the formation of alkaline hydration products in the artificial stone, inhibit efflorescence from the source, and at the same time has higher strength and wear resistance, and can achieve long-term inhibition of efflorescence from the source; it can be seen from Application Example 7 and Comparative Application Examples 3 and 4 that the lack of CaO or triethanolamine in the preparation of zinc-tungsten composite smelting slag will affect the comprehensive performance of the artificial stone.

[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An artificial stone anti-efflorescence material, characterized in that: The raw material components include, by weight: 17.0-27.5 parts by weight of cement, 19-39.5 parts by weight of slag powder, 2.5-12.5 parts by weight of gypsum, 30-50 parts by weight of zinc-tungsten composite smelting slag and 0.5-1.5 parts by weight of early strength agent; The zinc-tungsten composite smelting slag is prepared by adding CaO and triethanolamine to a mixed powder of zinc smelting slag and tungsten smelting slag.

2. The artificial stone anti-efflorescence material according to claim 1, characterized in that: The components of the zinc-tungsten composite smelting slag include zinc smelting slag and tungsten smelting slag; The components of the zinc-tungsten composite smelting slag include, by weight: 65-75 weight parts of zinc smelting slag and 25-35 weight parts of tungsten smelting slag; The specific surface area of ​​the zinc-tungsten composite smelting slag is 500±10㎡ / kg.

3. The artificial stone anti-efflorescence material according to claim 1, characterized in that: The amount of CaO added is 0.5%-1.5% of the total weight of the mixed powder; The added amount of the triethanolamine is 0.5%-1.5% of the total weight of the mixed powder.

4. The artificial stone anti-efflorescence material according to claim 1, characterized in that: The cement includes Portland cement.

5. The artificial stone anti-efflorescence material according to claim 1, characterized in that: The specific surface area of ​​the slag powder is 650±10㎡ / kg; The slag powder is obtained by grinding granulated blast furnace slag in a ball mill; The particle size of the granulated blast furnace slag is 2 μm-105 μm.

6. The artificial stone anti-efflorescence material according to claim 1, characterized in that: The gypsum includes at least one of dihydrate gypsum, desulfurized gypsum and phosphogypsum; The specific surface area of ​​the gypsum is 450±10㎡ / kg.

7. The artificial stone anti-efflorescence material according to claim 1, characterized in that: The early strength agent includes at least one of sodium sulfate, sodium hydroxide and calcium chloride.

8. The method for preparing the artificial stone anti-efflorescence material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The artificial stone anti-efflorescence material is obtained by mixing the formulated amounts of cement, slag powder, gypsum, zinc-tungsten composite smelting slag and early strength agent.

9. The preparation method according to claim 8, characterized in that: The zinc-tungsten composite smelting slag is prepared by the following steps: Adding CaO and triethanolamine to a mixed powder of zinc smelting slag and tungsten smelting slag, and grinding the mixture to obtain the zinc-tungsten composite smelting slag; Before mixing the zinc smelting slag and the tungsten smelting slag, the zinc smelting slag and the tungsten smelting slag are dried separately to a moisture content of ≤0.5%; During the preparation of the artificial stone anti-efflorescence material, the mixing time is ≥20 min.

10. Use of the artificial stone anti-efflorescence material according to any one of claims 1 to 7 in the preparation of artificial stone.